2008
DOI: 10.1542/peds.2007-2555
|View full text |Cite
|
Sign up to set email alerts
|

Bunk Bed–Related Injuries Among Children and Adolescents Treated in Emergency Departments in the United States, 1990–2005

Abstract: Bunk beds are a common source of injury among children and adolescents, and these injuries mostly involve the head and face. Given the continuing large numbers of bunk bed-related injuries at homes and in schools, increased efforts are needed to prevent bunk bed-related injuries among children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 19 publications
(64 reference statements)
2
16
0
Order By: Relevance
“…Consistent with our findings, previous studies on falls and playground injuries have shown that fractures (often to the upper limbs) are the most common type of injury, 2–5,9,10,13–30 that injury severity increases with height of fall, 1–4,16,17,20,21,23,26–28,31–33 and that boys are injured more often than girls 2–5,11,15–18,23,26,29,30,34–39 . Risk‐taking behavior has been found to be more common in males than in females and in older children compared with younger children 11 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our findings, previous studies on falls and playground injuries have shown that fractures (often to the upper limbs) are the most common type of injury, 2–5,9,10,13–30 that injury severity increases with height of fall, 1–4,16,17,20,21,23,26–28,31–33 and that boys are injured more often than girls 2–5,11,15–18,23,26,29,30,34–39 . Risk‐taking behavior has been found to be more common in males than in females and in older children compared with younger children 11 .…”
Section: Discussionsupporting
confidence: 91%
“…We also found that among falls, children <5 years of age had about five times greater odds of a head injury. This may be the result of younger children having larger heads and a higher center of gravity, which predisposes them to fall head first 9,15,27,40,41 …”
Section: Discussionmentioning
confidence: 99%
“…For example, Thompson et al 32 reported on an estimated 64 657 (3232 per year) inflatable bounce house injuries over a 20-year period ending in 2010. D'Souza et al 21 reported on an estimated 572 580 (35 786 injuries annually) bunk bed injuries over a 16-year period ending in 2005. Injuries associated with ladders were also reported by D'Souza with an estimated 2 177 888 injuries in the USA over a 16-year period ending in 2005 33.…”
Section: Discussionmentioning
confidence: 99%
“…NEISS is a publicly available database overseen by the US Consumer Product Safety Commission (CPSC). NEISS has been used to explore injuries from a wide variety of products, including those from recreational activities including mountain biking,15 unicycles16 and water tubing17; occupational injuries from ladders18 and nail guns,19 and home injuries including hot tubs20 and bunk beds 21. Although focused on consumer product-related injuries, NEISS also captures information about injuries more broadly, and thus, can help identify hazardous conditions in the home 22.…”
Section: Introductionmentioning
confidence: 99%
“…Bed-related injuries are already considered a social problem in Europe and the USA, with reports of some common characteristics of bed-related injuries. 10,11 First, most were due to falling and hitting the floor or objects around the bed; this is especially true among children younger than 6 years. Second, the most common injuries were head and facial lacerations.…”
Section: Possible Explanations and Implicationsmentioning
confidence: 99%